A probabilistic procedure to describe site amplification factors for seismic design codes. Issue 126 (November 2019) - Sandıkkaya, M. Abdullah; Akkar, Sinan; Bard, Pierre-Yves
Abstract: We introduce a site factor computation method for a region by extending the site-specific and probabilistic site amplification approach in Bazzuro and Cornell (2004). The site-factor exceedance probability is estimated from the exceedance probabilities of the reference rock ground motion and the soil amplification conditioned on the reference rock ground motion. The former probability is represented by regional hazard curves. The latter probability is computed from soil amplification models. The proposed method is capable of yielding site factors for a target exceedance probability. This property does not exist in the current code-based site factors. Given a site class, if the site factors and the reference rock spectrum possess the same exceedance probability the resulting spectrum would have the same probability of exceedance. The use of such probabilistically consistent earthquake demands would be more relevant for probability-based seismic design and assessment. Owing to the use of hazard curves, the proposed method can account for regional seismicity in the computation of site factors. Highlights: Examines Eurocode 8 and NEHRP site factors. Period dependency and nonlinear soil behavior should be considered in site factors. Computes probabilistically the hazard-consistent site factors for a region. NEHRP site factors are found sufficient but more realistic site factors are computed.